Worry, Risk Perception, and Controllability Predict Intentions Toward COVID-19 Preventive Behaviors - Sobkow, Agata; Zaleskiewicz, Tomasz; Petrova, Dafina; Garcia-Retamero, Rocio; Traczyk, Jakub (Frontiers in Psychology, 2020)
The ongoing pandemic of COVID-19 has already had serious worldwide health, socio-economic, political, and educational consequences. In the present study, we investigated what factors can motivate young adults to comply with the recommended preventive measures against coronavirus infection. Even though young people are less likely to suffer severe medical consequences from the virus, they can still transmit it to more vulnerable individuals. Surprisingly, we found no significant effects of previously successful experimental manipulations (i.e., positive mental imagery, enhancing self-efficacy, and visual aids) that aimed to improve risk understanding and impact COVID-19 related behavioral intentions. Instead, intentions towards preventive behaviors were predicted by self-reported worry, perceived controllability of the pandemic, and risk perception. Interestingly, worry about health and worry about restricting personal freedom, predicted behavioral intentions in diverging directions. In particular, participants who were worried about health, were more willing to obey strict hygiene and social distancing restrictions. In contrast, participants who were worried about personal restrictions, were less ready to adopt these preventive actions.